Propofol Inhibits Cerebellar Parallel Fiber-Purkinje Cell Synaptic Transmission via Activation of Presynaptic GABAB Receptors in vitro in Mice - Xuan, Fang-Ling; Wang, Hong-Wei; Cao, Li-Xin; Bing, Yan-Hua; Chu, Chun-Ping; Jin, Ri; Qiu, De-Lai (Frontiers in Neuroscience, 2018)
Propofol is a widely used intravenous sedative-hypnotic agent, which causes rapid and reliable loss of consciousness via activation of γ -aminobutyric acid A (GABAA) receptors. We previously found that propofol inhibited cerebellar Purkinje cells (PC) activity via both GABAA and glycine receptors in vivo in mice. We here examined the effect of propofol on the cerebellar parallel fiber (PF)-PC synaptic transmission in mouse cerebellar slices by whole-cell recording technique and pharmacological methods. We found that following blockade of GABAA and glycine receptors activity, propofol reversely decreased the amplitude of PF-PC excitatory postsynaptic currents (PF-PC EPSCs), and significantly increased paired-pulse ratio (PPR). The propofol-induced decrease in amplitude of PF-PC EPSCs was concentration-dependent. The half-inhibitory concentration (IC50) of propofol for inhibiting PF-PC EPSCs was 4.7 μM. Notably, the propofol-induced changes in amplitude and PPR of PF-PC EPSCs were abolished by GABAB receptor antagonist, saclofen (10 μM), but not blocked by N-methyl-D-aspartate receptor (NMDA) receptor antagonist, D-APV (50 μM). Application of the GABAB receptor agonist baclofen induced a decrease in amplitude and an increase in PPR of PF-PC EPSCs, as well masked the propofol-induced changes in PF-PC EPSCs. Moreover, the propofol-induced changes in amplitude and PPR of PF-PC EPSCs were abolished by a specific protein kinase A (PKA) inhibitor, KT5720. These results indicate that application of propofol facilitates presynaptic GABAB receptors, resulting in a depression of PF-PC synaptic transmission via PKA signaling pathway in mouse cerebellar cortex. The results suggest that the interaction with GABAB receptors may contribute to the general anesthetic action of propofol.